Right-wing populist parties and environmental politics: insights from the Austrian Freedom Party's support for the glyphosate ban. Issue 1 (23rd February 2021) - Tosun, Jale; Debus, Marc
ABSTRACT: Why has the right-wing populist Freedom Party of Austria supported a total glyphosate ban proposed by the Social Democratic Party? We examine this research question and pursue two goals: first, to explain the specific empirical puzzle; second, to develop a general argument on the environmental policy profile of right-wing populist parties. We contend that certain environmental issues and the way that policymaking handles them provide this party family with an opportunity for maximising its vote share. The parties might adopt – in specific contexts underlining their character as a right-wing populist party – strict stances on environmental issues. In the case of glyphosate, the Freedom Party could promise benefits to domestic groups, indicate the misconduct of (foreign) companies in the process of risk assessment and question the integrity of scientists. For these reasons, the party joined a coalition of parties demanding a glyphosate ban.